2007
DOI: 10.1200/jco.2007.25.18_suppl.5015
|View full text |Cite
|
Sign up to set email alerts
|

Randomised prospective study of intermittent versus continuous androgen suppression in advanced prostate cancer

Abstract: 5015 Background: Based on results of animal experiments intermittent androgen blockade was suggested to delay progression of advanced prostate cancer to the hormone refractory stage. We conducted a prospective randomized study to compare intermittent with continuous androgen suppression. Methods: This was a multi-centre, randomised, two-arm study comparing treatment with goserelin + bicalutamide (intermittent, group A) vs. goserelin + bicalutamide (continuous, group B). The primary endpoint was time to clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
2
4

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 0 publications
1
42
2
4
Order By: Relevance
“…We identified and reviewed publications from 25 IAD studies; of these, 13 were selected for the present literature review based on their relevance to assess safety and tolerability of IAD (Tables 2,3). Of these 13 studies, eight were randomized , active-controlled studies comparing IAD with CAD (Table 2; n = 68 to 1386 patients), 28,29,[31][32][33][34][35][36][37][38][39] and five were observational, non-randomized studies ( Table 3; n = 19 to 250 patients). 9,[40][41][42][43] Of these eight active-controlled studies, two 31,32 were published in full, whereas preliminary results have been reported in abstract format for the remaining six studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified and reviewed publications from 25 IAD studies; of these, 13 were selected for the present literature review based on their relevance to assess safety and tolerability of IAD (Tables 2,3). Of these 13 studies, eight were randomized , active-controlled studies comparing IAD with CAD (Table 2; n = 68 to 1386 patients), 28,29,[31][32][33][34][35][36][37][38][39] and five were observational, non-randomized studies ( Table 3; n = 19 to 250 patients). 9,[40][41][42][43] Of these eight active-controlled studies, two 31,32 were published in full, whereas preliminary results have been reported in abstract format for the remaining six studies.…”
Section: Resultsmentioning
confidence: 99%
“…9,[40][41][42][43] Of these eight active-controlled studies, two 31,32 were published in full, whereas preliminary results have been reported in abstract format for the remaining six studies. 29,33,[35][36][37][38]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized comparative clinical trials have been conducted to compare the efficacy between intermittent and continuous androgen suppression (Table 3). [27][28][29][30][31][32][33][34] At the present time, while only a few trials have obtained the final results, 27 no report has demonstrated a significantly worse time to progression and survival with intermittent androgen suppression than with continuous androgen suppression. On the other hand , most trials have indicated that the benefits of intermittent therapy were fewer adverse effects and increased quality of life.…”
Section: Randomized Clinical Trials Comparing Intermittent Vs Continumentioning
confidence: 99%
“…Randomized control trials comparing intermittent vs continuous androgen suppression[27][28][29][30][31][32][33][34] …”
mentioning
confidence: 99%